Pengaruh Spirulina terhadap VEGF dari Trofoblast Tikus Putih Hamil Strain Wistar yang Diinduksi Interleukin 6 - Harry K Gondo; Elizabeth Haryanti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Preeclampsia is a pregnancy disorder with hypertension as one of its common symptoms. Preeclampsia in pregnancy is characterized by increasing of proteinuria, blood pressure and also interleukin 6. Spirulina sp is a thread like shaped blue-green algae, similar to chain of cylindrical cells with 1 to 12 μm diameter of cell membrane. The purpose of this research was to know the effect of spirulina on VEGF level in improving of trophoblast function in pregnant white Rats Wistar. The design of the study was laboratory experimental with post-test only control group design. Twenty-five rats with preeclampsia model induced by interleukin 6, were divided into 5 groups. The groups were control group, positive control group (P0) injected by interleukin-6 dose of 5 ng/ 100 gram body weight (BW), group with spirulina dose of 10 mg/100 gram BW (P1), group with spirulina dose of 20 mg/100 gram BW (P2); and group with spirulina dosage 40 mg/100 gram BW (P3). The Vascular endothelial growth factor (VEGF) levels were in experimental groups measured compared to control. The averages of group spirulina were 81.31 (10 mg/100 gram BW), 65.99 (20 mg/100 gram BW), and 49.62 (40 mg/100 gram BW). In comparison with control group (62.70), VEGF level in group administered by spirulina dose of 20 mg/100 gram BW were close to control group.